MODEL FOR DETERMINATION OF CHARACTERISTICS OF RAILWAY TRAIN REGIME MAPS (Transport systems and technologies, 2021)
The article considers the issues of determining rational approaches to the creation of train maps, the rational use of diesel modes and the use of automated computer simulation system. Based on the obtained results, an energy-efficient mode of train driving is proposed and a mathematical model of the locomotive operation character is created. There is a need to review obsolete regime and train locomotive crews in the latest methods of operation. The basic values and methods of calculation for specific operating conditions on the basis of the law of conservation of mechanical energy are established. It is proposed to create a passport of each locomotive to determine the rational weight norms on the existing service shoulders. After all, overloading or underutilization of the locomotive's resource is associated with loss of profit or the emergence of emergencies. The necessity of the offered methods within the limits of ecological requirements to traction rolling stock is proved. The possibility of forming a rational system of mileage between technical inspections and repairs for each locomotive as a whole on the basis of forecasting and statistics is determined. It is recommended to further implement mathematical modeling and digital means of monitoring the technical condition after repairs to achieve economic efficiency of railway transport.
Keywords: automatic system, traction calculations, mode map, mathematical modeling, locomotive.